EFL students’ engagement in iSpring-facilitated listening activities. A study at a high school in Kien Giang - Lê Thị Thanh Phương (Trường Đại học Trà Vinh, 2023)
The general purpose of the present study is to investigate EFL students’ engagement in iSpring-facilitated listening activities, which might help students improve their listening performance and have positive attitudes towards using iSpring-facilitated listening activities. In particular, the objectives of the present study are to address problems related to time limitation and students’ engagement so that students will have more opportunities to attain the knowledge and skills related to what they should focus on in pre-, during-, and post-listening activities.